Breaking ground on ADHD diagnosis in Pakistan - Arysha Javid; Minahel Ahmed; Eman Sikandar (Journal of the Pakistan Medical Association, 2024)
Madam, Attention-deficit hyperactivity disorder – better known as ADHD - is a prevalent childhood behavioural disorder, estimated to have a prevalence between 2-7% globally [1]. Despite this high prevalence and its rising number of annual cases, ADHD underdiagnosed, especially in adolescent females and older children [1]. Undiagnosed ADHD has adverse effects on many aspects of a person’s life, including, but not limited to, social skills, time perception, stress management, and mood disorders. Meta-analysis evidence shows that childhood ADHD confers an elevated risk for depression across clinic-referred and community-based samples (Meinzer, Pettit, & Viswesvaran, 2014) [2]. Consequently, these patients face academic underachievement, hindrance in employment, relationships troubles and in extreme cases, criminality. A study published in PLOS One established that despite early onset and greater prevalence of ADHD in young males, symptoms tend to diminish compared to that of females [3]. It is proposed that ADHD in adult males is characterised by a lesser recognised form that does not include hyperactive-impulsive symptoms and, therefore, has more chance of going undiagnosed and unrecorded. This explains why it seems as if ADHD symptoms tend to diminish in males [3]. Newer research also speculates that a subset of women might be presenting with an adult-onset form of ADHD [3], contradicting historical concepts that ADHD is a neurodevelopmental disorder that always emerges in childhood. That being said, a possibility remains that the increased number of cases in adult women might just be undiagnosed women ’catching up’, supported by a review study that concluded increased ADHD identification in adult women compared to during childhood [2]. Pakistan has a severe lack of research and awareness regarding neurodivergence and ADHD. This explains why diagnosis and therapy for these patients using standardized behavioural rating scales and complete psychological evaluation is highly uncommon. The medical community of Pakistan needs to combat this by breaking the stigma surrounding neurodivergence and raising awareness about what ADHD is and what challenges it poses to undiagnosed patients. Early-on primary school screening of children can increase diagnosis and promote the provision of better opportunities to neurodivergent individuals to improve their standard of educational and work life.